(untitled) - Silverman, Sarah; Pace, Lee; 1979-; Ziegler, Maddie; Norris, Dean; Giacchino, Michael; Stitt, Kevin; Schwartzman, John; 1960-; Tremblay, Jacob; Lieberher, Jaeden; Kimmel, Sidney; et al. (Universal City, CA, 2017)
A single mother discovers a scheme in her sons book to rescue a young girl from the hands of her abusive stepfather and sets out to execute the plan at any cost.
Keywords: Drama; Rescues; Drama; Child abuse; Drama; Genius; Drama; Mothers and sons; Drama; Single mothers; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Thrillers (Motion pictures); Crime films; Fiction films; Feature films